Structural investigations on quinone methides for understanding their properties in confined media. - Szarma, R.J.; Batsanov, A.S.; Kataky, R.; Baruah, J.B. (Journal of Inclusion Phenomena and Macrocyclic Chemistry, 2025)
Encapsulation of 4−[(4′-hydroxy−3′,5′-dimethylphenyl)(aryl)-methylene]−2,6−dimethyl-cyclohexa−2,5−dienones (when aryl=4−hydroxyphenyl 1, 4−methoxyphenyl 2, 2,3,4-trimethoxy phenyl 3) by β-cyclodextrin is studied. The compound 2 is selectively encapsulated by β-cyclodextrin. The result is rationalised by analysing the structural parameters from the crystal structure of 1–3. The visible spectra of the compounds 2 and 3 at pH 9.0 show red shifts on the absorption maxima upon addition of cetyltrimethylammonium bromide (CTAB). For example, addition of a solution of CTAB to aqueous ethanolic solution of 2 at pH 9 causes shift of the absorption at 578–593 nm (Δλmax=15 nm). The advantage of this observation is taken to use 2 and 3 to determine the critical micelle concentration of CTAB in basic medium.
Keywords: Critical micelle concentration; Crystal structures; Cyclodextrin; Encapsulation; Quinone-methides.